THE INFLUENCE OF STANDARD OPERATIONAL PROCEDURE, WORK ENVIRONMENT, AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE OF PT. KERETA API INDONESIA OPERATIONAL AREA 8 GUBENG SURABAYA - Muhammad, Rachman Bin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of Standard Operating Procedures (SOP), Work Environment, and Organizational Culture on Employee Performance at PT. Kereta Api Indonesia (Persero) Operational Area 8 Gubeng Surabaya. In the current era of globalization and digital transformation, human resources play a critical role in achieving an organization’s strategic objectives. Optimal employee performance is not solely determined by individual abilities but is significantly influenced by structured work systems, embedded organizational culture, and a supportive work environment. The research is based on the phenomenon of unequal employee performance across divisions within the company. While the Passenger Facilities Division achieves high performance scores, the Freight Transport Division records lower performance, suggesting imbalances in the implementation of internal management factors such as SOP adherence, workplace conditions, and cultural values. Some organizational practices such as SOP enforcement and organizational culture are seen as being implemented formally without meaningful integration into daily operations, thus impacting employee effectiveness. A quantitative research approach was applied using multiple linear regression analysis. The population consists of employees of PT. KAI Daop 8 Surabaya, with purposive sampling used to collect responses. The research instrument was a validated and reliable questionnaire, and data were analyzed through classical assumption tests, the coefficient of determination (R²), F-tests (simultaneous), and t-tests (partial) to assess the relationship between the independent and dependent variables. The results show that SOP, work environment, and organizational culture have a significant simultaneous effect on employee performance. Individually, each variable positively contributes to performance, with SOP having the most dominant influence.